A review on the updated checklists of the amphibians and reptiles of Pakistan: Present and prehistoric - Amtyaz Safi; Hans-Volker Karl (Journal of Biodiversity and Biotechnology, 2024)
Recent herpetological collections have added several new taxa to the previously compiled herpetofauna of Pakistan. This paper presents annotated and updated checklists of 243 species, 104 genera, and 27 families of extant herpetofauna, including 24 anuran amphibian species, belonging to 4 families. In comparison, the reptilian fauna consists of 219 species/subspecies, including 2 species of crocodiles, 15 species of turtles and tortoises, 119 species of Sauria, and 83 species of snakes belonging to 23 families. Four species of amphibians and 33 species of reptiles are endemic to Pakistan. Separate checklists of prehistoric reptiles (50 taxa) for both dinosaurs (26 taxa) and non-dinosaurian taxa (24 taxa) are also presented here. This review article is based on previous literature on the herpetofauna of Pakistan. It will serve as a baseline for future work related to the herpetofauna of Pakistan, which is essential in biodiversity research.